2016
DOI: 10.1242/jeb.149336
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous alternation behavior in larval zebrafish

Abstract: Spontaneous alternation behavior (SAB) describes the tendency of animals to alternate their turn direction in consecutive turns. SAB, unlike other mnestic tasks, does not require any prior training or reinforcement. Because of its close correlation with the development and function of the hippocampus in mice, it is thought to reflect a type of memory. Adult zebrafish possess a hippocampus-like structure utilizing the same neurotransmitters as in human brains, and have thus been used to study memory. In the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…This is likely related to how spontaneous alternation has evolved into a standard test for memory in transgenic rodent models of human conditions (e.g., O'Leary, Hussin, Gunn, & Brown, ; Snider & Obrietan, ) or evaluating effects of pharmacological agents (Hughes, ). However, spontaneous alternation has been observed in several other nonhuman organisms, including larval zebrafish (Bögli & Huang, ) and black molly fish (Creson, Woodruff, Ferslew, Rasch, & Monaco, ), ants (Czaczkes, Koch, Fröber, & Dreisbach, ), fruit flies ( Drosophila melanogaster ; Lewis, Negelspach, Kaladchibachi, Cowen, & Fernandez, ), paramecium (Harvey & Bovell, ), marmosets (Izumi, Tsuchida, & Yamaguchi, ), and in some species of crab (but not others—Balcı, Ramey‐Balcı, & Ruamps, ; Ramey, Teichman, Oleksiak, & Balci, ). In other species, evidence for spontaneous alternation behavior is debatable (lemurs, Dal‐Pan et al, ; chicks, Hayes & Warren, ; hens, Haskell, Forkman & Waddington, ) or contrary (e.g., pigeons, Hughes, ).…”
Section: Exploring Similarities and Differencesmentioning
confidence: 99%
“…This is likely related to how spontaneous alternation has evolved into a standard test for memory in transgenic rodent models of human conditions (e.g., O'Leary, Hussin, Gunn, & Brown, ; Snider & Obrietan, ) or evaluating effects of pharmacological agents (Hughes, ). However, spontaneous alternation has been observed in several other nonhuman organisms, including larval zebrafish (Bögli & Huang, ) and black molly fish (Creson, Woodruff, Ferslew, Rasch, & Monaco, ), ants (Czaczkes, Koch, Fröber, & Dreisbach, ), fruit flies ( Drosophila melanogaster ; Lewis, Negelspach, Kaladchibachi, Cowen, & Fernandez, ), paramecium (Harvey & Bovell, ), marmosets (Izumi, Tsuchida, & Yamaguchi, ), and in some species of crab (but not others—Balcı, Ramey‐Balcı, & Ruamps, ; Ramey, Teichman, Oleksiak, & Balci, ). In other species, evidence for spontaneous alternation behavior is debatable (lemurs, Dal‐Pan et al, ; chicks, Hayes & Warren, ; hens, Haskell, Forkman & Waddington, ) or contrary (e.g., pigeons, Hughes, ).…”
Section: Exploring Similarities and Differencesmentioning
confidence: 99%
“…Finally, this study also showed that noise-exposed 5 dpf larvae (under CN 150 ) displayed impaired innate Spontaneous Alternation Behaviour compared to control individuals. Bögli et al, (2017) 87 effectively established the presence of SAB in larval zebra sh (6 dpf) suggesting the presence of early mnestic capabilities. At this developmental stage (4 to 5 dpf), the hippocampal-like pallium develops 88 , and this brain structure is known to be related with navigation and spatiotemporal sensing in shes 89,90 .…”
Section: Discussionmentioning
confidence: 97%
“…Larval zebra sh were further tested regarding the Spontaneous Alternation Behaviour (SAB), which consists on the tendency of animals to alternate their movement directions in consecutive turns when navigating through their environment. The SAB was assessed in a 3D printed T-maze designed based on Bögli and Huang (2017) 107 and consisted in two starting arms converging into a main arm that bifurcated in the end into two goal arms, each leading to a pool (Fig. 5A).…”
Section: Spontaneous Alternation Behaviour Assaymentioning
confidence: 99%
“…This is likely related to how spontaneous alternation has evolved into a standard test for memory in transgenic rodent models of human conditions (e.g., O'Leary, Hussin, Gunn, & Brown, 2018;Snider & Obrietan, 2018) or evaluating effects of pharmacological agents (Hughes, 2004). However, spontaneous alternation has been observed in several other nonhuman organisms, including larval zebrafish (Bögli & Huang, 2017) and black molly fish (Creson, Woodruff, Ferslew, Rasch, & Monaco, 2003), ants (Czaczkes, Koch, Fröber, & Dreisbach, 2018), fruit flies (Drosophila melanogaster; Lewis, Negelspach, Kaladchibachi, Cowen, & Fernandez, 2017), paramecium (Harvey & Bovell, 2006), marmosets (Izumi, Tsuchida, & Yamaguchi, 2013), and in some species of crab (but not others-Balcı, Ramey-Balcı, & Ruamps, 2014;Ramey, Teichman, Oleksiak, & Balci, 2009). In other species, evidence for spontaneous alternation behavior is debatable (lemurs, Dal-Pan et al, 2011;chicks, Hayes & Warren, 1963;hens, Haskell, Forkman & Waddington, 1998) or contrary (e.g., pigeons, Hughes, 1989).…”
Section: Comparative (Phylogeny)mentioning
confidence: 99%